1996
DOI: 10.1182/blood.v88.3.785.785
|View full text |Cite
|
Sign up to set email alerts
|

TEL-AML1 translocations with TEL and CDKN2 inactivation in acute lymphoblastic leukemia cell lines

Abstract: The t(12;21) (p 13; q22) results in the fusion of the TEL gene located on chromosome 12 with the AML1 gene located on the derivative chromosome 21. Because this translocation is difficult to detect using standard cytogenetic techniques, 27 previously karyotyped B-lineage acute lymphoblastic leukemia (ALL) cell lines were evaluated for the presence of the TEL-AML1 fusion using the reverse transcriptase- polymerase chain reaction (RT-PCR), fluorescence in situ hybridization (FISH), and cDNA sequencing. Six cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…For this reason, we included in this cohort three cases with simultaneous aberrant near‐diploid and/or pseudodiploid metaphases. These findings indicate that tetraploidization could be one of the steps involved during the multistep developmental process of leukemic clones in NT‐ALL probably associated with a growth advantage (10, 23). The tetraploid clone was even lost or overgrown by a related new pseudodiploid clone at 2nd relapse in one patient supporting further this hypothesis.…”
Section: Discussionmentioning
confidence: 85%
“…For this reason, we included in this cohort three cases with simultaneous aberrant near‐diploid and/or pseudodiploid metaphases. These findings indicate that tetraploidization could be one of the steps involved during the multistep developmental process of leukemic clones in NT‐ALL probably associated with a growth advantage (10, 23). The tetraploid clone was even lost or overgrown by a related new pseudodiploid clone at 2nd relapse in one patient supporting further this hypothesis.…”
Section: Discussionmentioning
confidence: 85%
“…In our research, there were only a few patients with TEL/AML1 and hypodiploidy and even fewer in CDKN2 deletion carriers. Kim found that ALL cell lines with TEL/AML1 fusion gene and deletion of 9p21 had a strong ability to proliferate compared with the cell lines with TEL/AML1 fusion gene only 28 , and deletion of 9p21 may weakened or even reverse the favorable impact of the TEL/AML1 fusion proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…(Table S1). The HB11;19 cell line was kindly provided by Dr. Anthony Ford from the Institute of Cancer Research (London, UK), and the UOC-B6 cell line was provided by Dr Ondrej Krejci (Massachusetts General Hospital, Boston) (14). The rest of the cell lines were purchased from German Collection of Microorganisms and Cell Cultures (DSMZ, Braunschweig, Germany;).…”
Section: Introductionmentioning
confidence: 99%